Pengaruh Pelatihan Manajemen Diri dan Konsep Diri Terhadap Hasil Belajar Mata Kuliah Manajemen Pendidikan - Iskandar Iskandar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2017)
This study aims at revealing the effect of self-management training on learning outcomes of Management Education courses At the History study program students of KIP Tadulako University. This research used experimental method with design treatment by level 2 x 2, data analysis was ANAVA to prove 4 hypotheses. The result showed that 1) students learning outcomes which were given the self-management training is higher than the student who were given self-efficacy training; 2) there is the influence of interaction between self-management and self-concept on learning outcomes of education management; 3) learning outcomes of students who have positif self-concept is higher than learning outcomes of students who have a negative self-concept even though both were given self-management training; 4) learning outcomes of students who have a negative self-concepthigher than learning outcomes of students who have positive self-concept even though both were given self-efficacy training.